2013 IEEE International Conference on Solid Dielectrics (ICSD) 2013
DOI: 10.1109/icsd.2013.6619812
|View full text |Cite
|
Sign up to set email alerts
|

Electrical treeing from needle implants in XLPE during very low frequency (VLF) voltage testing

Abstract: This paper presents results from experimental investigations performed in order to characterize electrical treeing as a function of frequency and magnitude of the applied ac voltage. All tests were performed using steel needles molded into 2 mm thick samples of cross-linked polyethylene (XLPE) with an insulation distance of 1 mm. The formation of electrical trees from the energized needle tips were studied using optical microscopy video techniques and characterized with respect to growth rate and maximum tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The cause for fibrillar type damage could be due to high packing density of the material (due to shrinkage of material) at low temperature and fast quenching of local temperature rise occurred due to partial discharge activity, the amount of damage to the insulating material gets reduced thereby forming thin fibrillar type damage than voluminous damage that occurs in same material at room temperature [17]. It is also observed with higher order harmonics with increased THD, the diameter of the main branch is reduced and more of fibrillar type structure forms.…”
Section: Characterization Of Trees Formed Under Harmonic Ac Voltagementioning
confidence: 98%
See 1 more Smart Citation
“…The cause for fibrillar type damage could be due to high packing density of the material (due to shrinkage of material) at low temperature and fast quenching of local temperature rise occurred due to partial discharge activity, the amount of damage to the insulating material gets reduced thereby forming thin fibrillar type damage than voluminous damage that occurs in same material at room temperature [17]. It is also observed with higher order harmonics with increased THD, the diameter of the main branch is reduced and more of fibrillar type structure forms.…”
Section: Characterization Of Trees Formed Under Harmonic Ac Voltagementioning
confidence: 98%
“…To identify the formation of any defects during laying of high voltage cables, AC and DC tests were carried out [16] fundamental issue with the DC test is the formation of space charge in cable insulation and very low frequency test is identified as an alternative [17]. It is essential to understand the electrical tree formation in XLPE polymer insulation at low temperature under VLF voltages as well the rate of failure of XLPE polymer insulation with trees and its growth under VLF voltages.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that with frequency reduction, electrical trees grow slower and their shape is also affected. It has been reported that the time to breakdown at 0.1 Hz was three times longer than at 1 Hz [9] and trees grown at VLF (0.1 Hz) can be almost five times slower than industrial frequency (50 Hz) in test samples at the same high voltage level [11], showing that the tree growth rate is not linear with respect to the frequency. Moreover, electrical trees grown at VLF have a less bushy/dense structure compared to those grown at industrial frequencies [9], [11].…”
Section: Introductionmentioning
confidence: 98%
“…Electrical tree growth is affected by the frequency of the voltage excitation that is stressing the system [9]- [13]. Nowadays, electrical components of a power grid, and thus the dielectric systems that conform them, are subjected to a variety of frequencies due to the grid operation and nonlinear loads [14], or due to tests needed for commissioning and maintenance of equipment [15], [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation